Improved Enzymatic Hydrolysis of Pilot Scale Pretreated Rice Straw at High Total Solids Loading - Agrawal, Ruchi; Bhadana, Bharti; Mathur, A. S.; Kumar, Ravindra; Gupta, Ravi P.; Satlewal, Alok (Frontiers in Energy Research, 2018)
Enzymatic hydrolysis at high solids loading has the potential to reduce both capital and operational expenditures. Here, pretreatment of rice straw (PRS) with dilute acid was carried out at a pilot scale (250 kg per day) at 162°C for 10 min and 0.35% acid concentration, followed by enzymatic hydrolysis at different total solids loadings. It showed that although the total sugar concentration increased from 48 to 132 g/l, glucan conversion reduced by 27% (84–66.2%) with increasing solids from 5 to 20% in batch mode. Therefore, two different fed-batch approaches were evaluated to improve the glucan conversion by the sequential addition of a substrate and/or enzyme. At 20% solid loadings and a 3 filter paper units/g enzyme dosage, the highest glucan conversion obtained was 66% after 30 h of hydrolysis in batch mode. However, in an optimized fed-batch approach, the glucan yield was improved to 70% by simply dividing the substrate feeding into three batches, that is, 50% at 0 h, 25% each after 4 h, and 8 h of hydrolysis reaction. The addition of surfactant (Ecosurf E6) further improved the conversion to 72% after 30 h. The role of critical factors, that is, inhibitors, enzyme–lignin binding, and viscosity, was investigated during the course of hydrolysis in the batch and fed-batch approaches. This study suggests a sustainable approach for improved hydrolysis at high solids loadings by fine-tuning a simple process.